Jihadist Movements in the Sahel: Rise of the Fulani? - Cline, Lawrence E. (Terrorism and political violence, 2023)
Much of the attention paid to jihadist groups in the greater Sahel region have focused on the Tuareg movements. More recently, however, members of the Fulani ethnic group have become much more significant in the larger jihadist movement in the region. The Fulani-dominated Katiba Macina and Ansarul Islam have conducted major attacks and created a significant level of civilian displacement. Many of the Fulani operations to date clearly are a continuation of their earlier conflicts both with regional governments and other ethnic groups. The increased identification of the Fulani in the jihadist movement also provides a further example of how preexisting group grievances can be operationalized by leaders of violent groups into an ideological movement.